Gender Sensitive Adult Education: Critical Perspective - Ostrouch-Kamińska, Joanna; Vieira, Cristina C. (Revista Portuguesa de Pedagogia, 2016)
This article aims to foster a reflection on the meaning of gender in adults’ learning, considering gender as a social order that is entrenched in daily relations, no matter the domain of life under analyses. As the research shows, it cannot be any longer ignored that being a man or a woman creates a different approach of the learner towards the situation of learning, mainly because formal, informal and non-formal contexts of learning tend to be congruent with a set of messages based on gender stereotypes that can be prejudicial to the individual’s development. The experiences related to gender influence the way knowledge is acquired, the expectations people make about themselves, the choices of learning subjects and their self-confidence in learning. The use of gender lenses to deconstruct such learned norms should be included in the field of adult education as a way of promoting (social) subjectivity of contemporary adult learners.